OPTIMALISASI MANAGEMEN BERBASIS MADRASAH DALAM UPAYA PENGEMBANGAN MADRASAH ADIWIYATA DI MTSN 1 LAMPUNG TIMUR - Ruqoyah, Siti; Uliyah, Taqwatul; Iqbal , Riskun (UNISAN JURNAL, 2023)
Madrasah-Based Management (MBM). It is a new paradigm in managing madrasas, which involves the government, the community and the madrasas themselves. MBM gives greater autonomy to madrasa heads to plan, implement and adopt policies. Madrasahs implementing MBM must make a madrasah development plan. Madrasah development plans generally include the formulation of the vision, mission, objectives of the madrasa and its implementation strategy. Meanwhile, madrasah annual work plans generally include identifying madrasah goals (madrasah situational goals), selecting madrasah functions needed to achieve the identified goals, SWOT analysis, problem-solving steps, and preparing an annual madrasah work plan and program. The following describes briefly the formulation of the vision, mission, goals and objectives of the school (school situational goals). Madrasah Adiwiyata is a madrasah concept that cares for and loves the environment, which is comfortable, conducive so that the learning process can create madrasah citizens, especially students who care and are environmentally cultured, while simultaneously supporting and realizing human resources with national character towards economic, social and environment in achieving sustainable development in the region. On the basis of the problems above, the problem formulation that the authors propose in this study is to determine the implementation of Madrasah-Based Management in the Development of Adiwiyata Madrasahs at Madrasah Tsanawiyah Negeri 1 East Lampung in 2022. This type of research is evaluation research using qualitative research methods. According to Sugiyono, evaluation research is research that aims to compare an event, activity and product with established standards and programs, so that evaluation research functions to explain phenomena. Based on the results of observational interviews, and documentation regarding the implementation of madrasah-based management in the effort to develop Adiwiyata Madrasahs in 2022 at the planning and implementation stages, it is quite good.